1999
DOI: 10.1017/s0952523899166070
|View full text |Cite
|
Sign up to set email alerts
|

Models of receptive-field dynamics in visual cortex

Abstract: The position, size, and shape of the receptive field (RF) of some cortical neurons change dynamically, in response to artificial scotoma conditioning (Pettet & Gilbert, 1992) and to retinal lesions (Chino et al., 1992; Darian-Smith & Gilbert, 1995) in adult animals. The RF dynamics are of interest because they show how visual systems may adaptively overcome damage (from lesions, scotomas, or other failures), may enhance processing efficiency by altering RF coverage in response to visual demand, and may perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 89 publications
(248 reference statements)
2
4
0
Order By: Relevance
“…The outcome is either relative response gain or receptive-field expansion of neurons inside the scotoma rendering them selective to stimulation around the receptive field. Simulation studies also support the suggestion that cortical neurons selective to visual stimuli in the area of the visual field corresponding to the retinal lesion may become selective to other parts of the visual field (Xing & Gerstein, 1994;Kalarickal & Marshall, 1999, 2002Xing & Heeger, 2000;Andrade et al, 2001). If similar plasticity effects occurred in patients with central scotoma, they would probably lead to a relative modification in filtering properties of neurons in silenced cortical area, or else to a relative response gain.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…The outcome is either relative response gain or receptive-field expansion of neurons inside the scotoma rendering them selective to stimulation around the receptive field. Simulation studies also support the suggestion that cortical neurons selective to visual stimuli in the area of the visual field corresponding to the retinal lesion may become selective to other parts of the visual field (Xing & Gerstein, 1994;Kalarickal & Marshall, 1999, 2002Xing & Heeger, 2000;Andrade et al, 2001). If similar plasticity effects occurred in patients with central scotoma, they would probably lead to a relative modification in filtering properties of neurons in silenced cortical area, or else to a relative response gain.…”
Section: Introductionsupporting
confidence: 54%
“…In support of this suggestion, Braun et al (2001) showed that lesions in the peripheral visual system induce disinhibition due to changes in intracortical connectivity, resulting in increased cortical activity. Simulation studies also support the suggestion that cortical neurons selective to visual stimuli in the area of the visual field corresponding to the retinal lesion may become selective to other parts of the visual field (Xing & Gerstein, 1994;Kalarickal & Marshall, 1999, 2002Xing & Heeger, 2000;Andrade et al, 2001). The outcome is either relative response gain or receptive-field expansion of neurons inside the scotoma rendering them selective to stimulation around the receptive field.…”
Section: Introductionmentioning
confidence: 53%
“…Previous hypotheses to explain RF dynamics have proposed an adaptation of surround inhibition or a potentiation of horizontal connections by the prolonged scotoma presentation (Pettet and Gilbert, 1992;Xing and Gerstein, 1994;DeAngelis et al, 1995;Kalarickal and Marshall, 1999;Cavanaugh et al, 2002). Our results offer an alternative explanation, which is based on the adaptation state of the cells before RF measurements.…”
Section: Effects and Aftereffects Of Scotoma Presentationmentioning
confidence: 51%
“…The EXIN lateral inhibitory synaptic plasticity models dynamic RF changes produced by artificial scotoma conditioning and retinal lesions (Kalarickal andMarshall 1999, Marshall andKalarickal 1997). The EXIN rules have been used to model development of disparity selectivity (Marshall 1990c), motion selectivity and grouping (Marshall 1990a, 1995b, Schmitt and Marshall 1995, orientation selectivity (Marshall 1990d) and length selectivity and end-stopping (Marshall 1990b).…”
Section: Exin Model Of Rf Changesmentioning
confidence: 99%